Shape Memory Polymer Foams With Phenolic Acid-Based Antioxidant and Antimicrobial Properties for Traumatic Wound Healing - Du, Changling; Liu, Jingyi; Fikhman, David Anthony; Dong, Katheryn Shi; Monroe, Mary Beth Browning (Frontiers in Bioengineering and Biotechnology, 2022)
The leading cause of trauma-related death before arrival at a hospital is uncontrolled blood loss. Upon arrival at the hospital, microbial infections in traumatic wounds become an additional factor that increases mortality. The development of hemostatic materials with antimicrobial and antioxidant properties could improve morbidity and mortality in these wounds. To that end, phenolic acids (PAs) were successfully incorporated into the network of shape memory polymer (SMP) polyurethane foams by reacting them with isocyanates. Resulting PA-containing SMP foam shape memory properties, antimicrobial and antioxidant activity, and blood and cell interactions were characterized. Results showed that p-coumaric, vanillic, and ferulic acids were successfully incorporated into the SMP foams. The PA-containing SMP foams retained the antimicrobial and antioxidant properties of the incorporated PAs, with ~20% H2O2 scavenging and excellent antimicrobial properties again E. coli (~5X reduction in CFUs vs. control foams), S. aureus (~4.5X reduction in CFUs vs. control foams, with comparable CFU counts to clinical control), and S. epidermidis (~25-120X reduction in CFUs vs. control foams, with comparable CFU counts to clinical control). Additionally, appropriate thermal and shape memory properties of PA foams could enable stable storage in low-profile secondary geometries at temperatures up to ~55°C and rapid expand within ~2 minutes after exposure to water in body temperature blood. PA foams had high cytocompatibility (>80%), non-hemolytic properties, and platelet attachment and activation, with improved cytocompatibility and hemocompatibility in comparison with clinical, silver-based controls. The incorporation of PAs provides a natural non-antibiotic approach to antimicrobial SMP foams with antioxidant properties. This system could improve outcomes in traumatic wounds to potentially reduce bleeding-related deaths and subsequent infections.